Diversity of white Guinea yam (Dioscorea rotundata Poir.) cultivars from Benin as revealed by agro-morphological traits and SNP markers - Agre, A.P.; Dassou, A.G.; Loko, Y.; Idossou, R.; Dadonougbo, E.; Gbaguidi, A.A.; Mondo, J.; Muyideen, Y.; Adebola, P.O.; Asiedu, R.; Dansi, A.; Asfaw, A. (Cambridge University Press, 2021)
White Guinea yam (Dioscorea rotundata Poir.) is indigenous to West Africa, a region that harbours the crop's tremendous landrace diversity. The knowledge and understanding of local cultivars’ genetic diversity are essential for properly managing genetic resources, conservation, sustainable use and their improvement through breeding. This study aimed to dissect phenotypic and molecular diversity of white yam cultivars from Benin using agro-morphological and single nucleotide polymorphism (SNP) markers. Eighty-eight Beninese white Guinea yam cultivars collected through a countrywide ethnobotanical survey were phenotyped with 53 traits and genotyped with 9725 DArT-SNP. Multivariate analysis using phenotypic traits revealed 30 traits as most discriminative and explained up to 80.78% of cultivars’ phenotypic variation. Assessment of diversity indices such as Shannon–Wiener (H′), inverse Shannon (H.B.), Simpson's (λ) index and Pilou evenness (J) based molecular and phenotypic data depicted a moderate genetic diversity in Beninese white Guinea yam cultivars. Genetic differentiation of cultivars among country production zones was low due to the high exchange of planting materials among farmers of different regions. However, there was high genetic diversity within regions. Hierarchical clusters (HCs) on phenotypic data revealed the presence of two groups while HCs based on the SNP markers and the combined analysis identified three genetic groups. Our result provided valuable insights into the Beninese white Guinea yam diversity for its proper conservation and improvement through breeding.